A Case Study on Ayurvedic Management in Insulin Resistance in Polycystic Ovarian Disease (International Journal of Ayurveda and Pharma Research, 2023)
Polycystic ovarian disease is highly prevalent hormonal and metabolic disorder among reproductive aged women worldwide characterised by hyperandrogenism, chronic anovulation and polycystic ovaries. Insulin resistance is now recognised as a basic underlying pathology of PCOD and found in approximately 50-70% of patients. It is defined as a state in which greater than normal amounts of insulin are required to produce a quantitatively normal response. It is associated with an increased risk of various metabolic disorders including type 2 diabetes mellitus, hypertension, dyslipidaemia and cardiovascular diseases, which indicates that timely therapeutic intervention in PCOS could prevent or at-least delay the onset of type 2 diabetes mellitus and other long-term health risks. Most of the features of PCOD associated with insulin resistance can be found under Santharpanajanya vyadhis with involvement of three Doshas and Dhathus like Rasa, Raktha and Medus. Here is a case report of 18-year-old female who presented with irregular menstruation, rapid weight gain and blackish discoloration of back of neck. Her USG findings shows bilateral polycystic pattern of ovaries. Based on clinical features and laboratory values, treatment principles adopted are Agni deepana, Ama pachana, Vatha-kaphahara and Lekhana. Varanadi kashyam and triphala choorna with takra given internally for 3 months and Udwartana was done externally for 14 days. After 3 months of treatment considerable reduction in weight and improvement in insulin resistance were noticed and her menstrual periods were normal with normal USG findings. The present case signifies the importance of Ayurvedic management in insulin resistance of PCOD to prevent forthcoming complications.